Sport Development Index of Banyumas Regency - N, Ngadiman; Kusuma, Indra Jati; Festiawan, Rifqi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The purpose of this study was to evaluate the local governmentâ€™s success in its development, especially in the field of sports from the aspect of open space availability, community participation, sport resource, and community fitness level (Sport Development Index). Therefore, an evaluative research approach was employed in this study. The research employed both stratified random sampling and cluster sampling techniques. The population basic characteristics included the differences of regional progress level, gender between male and female, age ranging from children aged 7-12 year old, adolescents aged 13-17 year old, and adults aged 18-40 year old, while the basic cluster characteristics used were district and sub-district or village. The research results showed that the open space index was classified in low category (0.180), human resource index in medium category (0.551), public participation index in medium category (0.572), and physical fitness index in low category (0.488). Simultaneously, the Sport Development Index of Banyumas Regency in 2010 is classified in low category (0.487).Â Â